New species and a new record of Malaxis (Malaxidinae) from Costa Rica - Chinchilla Alvarado, Isler Fabián (2022)
We describe and illustrate a new species and a new record of Malaxis from the lower montane and montane forests of Costa Rica. Taxonomic descriptions, illustrations, distribution maps, and conservation assessments are provided for each species. Malaxis excentrica sp. nov. is morphologically similar to Malaxis simillima, from which it can be distinguished by having a single leaf per sympodial unit, shorter, obovate, erect petals parallel to the column, the lip with triquetrous, acute, convex apical margin and the disc cavity divided by a costa. Malaxis pittieri is formally recorded for the flora of Costa Rica; Costa Rican specimens of this species were previously confused with Malaxis majanthemifolia. A lectotype for Microstylis pittieri is formally designated.